Pemanfaatan Limbah Organik Sebagai Eco enzyme dalam Mengatasi Antraknosa pada Tanaman Cabai di Desa Kiarapandak, Bogor - Astrida Syahwa Nur Ashri; Silvia Nuraini; Amelia; Siti Amalia Agustin; Hafiz Damarjati; Septa Huda Marwah; Adinda Syifa Faulia; Athaya Firdaus; Dania Samoda Renda; Zuhri, Mahfuddin (Jurnal Pusat Inovasi Masyarakat, 2024)
Household waste management is one of the problems that remains unsolved to this day in Kiarapandak Village, Sukajaya Subdistrict, Bogor Regency. This problem is caused by the lack of optimal waste management, especially household waste. The Cozy (eco enzyme) program is executed as a form of public service in hopes to solve said problem by empowering the village community in managing household waste. This program is done through socialization about the utilization of household organic waste as eco enzyme, monitoring the eco enzyme product, and application of the eco enzyme on several plants. The plants that were given the eco enzyme showed good growth and are also protected from anthracnose. This program is considered to provide benefits to the community, especially farmers who are having troubles regarding anthracnose on chili plants.